# Calculator search results

Formula
Number of solution
Relationship between roots and coefficients
Graph
$y = 3 x ^ { 2 } + 6 x$
$y = 0$
$x$-intercept
$\left ( 0 , 0 \right )$, $\left ( - 2 , 0 \right )$
$y$-intercept
$\left ( 0 , 0 \right )$
Minimum
$\left ( - 1 , - 3 \right )$
Standard form
$y = 3 \left ( x + 1 \right ) ^ { 2 } - 3$
$3x ^{ 2 } +6x = 0$
$\begin{array} {l} x = 0 \\ x = - 2 \end{array}$
Find solution by method of factorization
$\color{#FF6800}{ 3 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 6 } \color{#FF6800}{ x } = 0$
$ax^{2} + bx = x\left(ax+b\right)$
$\color{#FF6800}{ 3 } \color{#FF6800}{ x } \left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 2 } \right ) = 0$
$\color{#FF6800}{ 3 } \color{#FF6800}{ x } \left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 2 } \right ) = \color{#FF6800}{ 0 }$
 If the product of the factor is 0, at least one factor should be 0 
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ 0 } \\ \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 2 } = \color{#FF6800}{ 0 } \end{array}$
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ 0 } \\ \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 2 } = \color{#FF6800}{ 0 } \end{array}$
 Solve the equation to find $x$
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ 0 } \\ \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 2 } \end{array}$
$\begin{array} {l} x = 0 \\ x = - 2 \end{array}$
Solve quadratic equations using the square root
$\color{#FF6800}{ 3 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 6 } \color{#FF6800}{ x } = \color{#FF6800}{ 0 }$
 Divide both sides by the coefficient of the leading highest term 
$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 2 } \color{#FF6800}{ x } = \color{#FF6800}{ 0 }$
$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 2 } \color{#FF6800}{ x } = \color{#FF6800}{ 0 }$
 Convert the quadratic expression on the left side to a perfect square format 
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 1 } \right ) ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 1 } ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ 0 }$
$\left ( x + 1 \right ) ^ { 2 } \color{#FF6800}{ - } \color{#FF6800}{ 1 } ^ { \color{#FF6800}{ 2 } } = 0$
 Move the constant to the right side and change the sign 
$\left ( x + 1 \right ) ^ { 2 } = \color{#FF6800}{ 1 } ^ { \color{#FF6800}{ 2 } }$
$\left ( x + 1 \right ) ^ { 2 } = \color{#FF6800}{ 1 } ^ { \color{#FF6800}{ 2 } }$
 Calculate power 
$\left ( x + 1 \right ) ^ { 2 } = \color{#FF6800}{ 1 }$
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 1 } \right ) ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ 1 }$
 Solve quadratic equations using the square root 
$\color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 1 } = \pm \sqrt{ \color{#FF6800}{ 1 } }$
$\color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 1 } = \pm \sqrt{ \color{#FF6800}{ 1 } }$
 Solve a solution to $x$
$\color{#FF6800}{ x } = \pm \color{#FF6800}{ 1 } \color{#FF6800}{ - } \color{#FF6800}{ 1 }$
$\color{#FF6800}{ x } = \pm \color{#FF6800}{ 1 } \color{#FF6800}{ - } \color{#FF6800}{ 1 }$
 Separate the answer 
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 1 } \color{#FF6800}{ + } \color{#FF6800}{ 1 } \\ \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 1 } \color{#FF6800}{ - } \color{#FF6800}{ 1 } \end{array}$
$\begin{array} {l} x = \color{#FF6800}{ - } \color{#FF6800}{ 1 } \color{#FF6800}{ + } \color{#FF6800}{ 1 } \\ x = - 1 - 1 \end{array}$
 Remove the two numbers if the values are the same and the signs are different 
$\begin{array} {l} x = 0 \\ x = - 1 - 1 \end{array}$
$\begin{array} {l} x = 0 \\ x = \color{#FF6800}{ - } \color{#FF6800}{ 1 } \color{#FF6800}{ - } \color{#FF6800}{ 1 } \end{array}$
 Find the sum of the negative numbers 
$\begin{array} {l} x = 0 \\ x = \color{#FF6800}{ - } \color{#FF6800}{ 2 } \end{array}$
 2 real roots 
Find the number of solutions
$\color{#FF6800}{ 3 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 6 } \color{#FF6800}{ x } = \color{#FF6800}{ 0 }$
 Determine the number of roots using discriminant, $D=b^{2}-4ac$ from quadratic equation, $ax^{2}+bx+c=0$
$\color{#FF6800}{ D } = \color{#FF6800}{ 6 } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ \times } \color{#FF6800}{ 3 } \color{#FF6800}{ \times } \color{#FF6800}{ 0 }$
$D = \color{#FF6800}{ 6 } ^ { \color{#FF6800}{ 2 } } - 4 \times 3 \times 0$
 Calculate power 
$D = \color{#FF6800}{ 36 } - 4 \times 3 \times 0$
$D = 36 - 4 \times 3 \color{#FF6800}{ \times } \color{#FF6800}{ 0 }$
 If you multiply a number by 0, it becomes 0 
$D = 36 + \color{#FF6800}{ 0 }$
$D = 36 \color{#FF6800}{ + } \color{#FF6800}{ 0 }$
 0 does not change when you add or subtract 
$D = 36$
$\color{#FF6800}{ D } = \color{#FF6800}{ 36 }$
 Since $D>0$ , the number of real root of the following quadratic equation is 2 
 2 real roots 
$\alpha + \beta = - 2 , \alpha \beta = 0$
Find the sum and product of the two roots of the quadratic equation
$\color{#FF6800}{ 3 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 6 } \color{#FF6800}{ x } = \color{#FF6800}{ 0 }$
 In the quadratic equation $ax^{2}+bx+c=0$ , if the two roots are $\alpha, \beta$ , then it is $\alpha + \beta =-\dfrac{b}{a}$ , $\alpha\times\beta=\dfrac{c}{a}$
$\color{#FF6800}{ \alpha } \color{#FF6800}{ + } \color{#FF6800}{ \beta } = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 6 } { 3 } } , \color{#FF6800}{ \alpha } \color{#FF6800}{ \beta } = \color{#FF6800}{ \dfrac { 0 } { 3 } }$
$\alpha + \beta = - \color{#FF6800}{ \dfrac { 6 } { 3 } } , \alpha \beta = \dfrac { 0 } { 3 }$
 Reduce the fraction 
$\alpha + \beta = - \color{#FF6800}{ 2 } , \alpha \beta = \dfrac { 0 } { 3 }$
$\alpha + \beta = - 2 , \alpha \beta = \color{#FF6800}{ \dfrac { 0 } { 3 } }$
 If the numerator is 0, it is equal to 0 
$\alpha + \beta = - 2 , \alpha \beta = \color{#FF6800}{ 0 }$
 그래프 보기 
Graph
Solution search results